2014
DOI: 10.1016/j.foodres.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the water distribution and extractable sugar content in carrot slices after pulsed electric field treatment

Abstract: The impact of pulsed electric field (PEF) processing conditions on the distribution of water in carrot tissue and extractability of soluble sugars from carrot slices was studied. Time domain NMR relaxometry was used to investigate the water proton mobility in PEF-treated carrot samples. Three distinct transverse relaxation peaks were observed in untreated carrots. After PEF treatment only two slightly-overlapping peaks were found; these were attributed to water present in the cytoplasm and vacuole of carrot xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, changes in cell walls could also cause differences in the water absorbed into the polysaccharides network which affect other textural and sensory perception properties. [49] Electropermeabilisation and cytoplasmic content leakage could also increase adhesiveness of PEF-treated carrots since Aguiló-Aguayo et al [50] reported that cellular content moved from vacuoles to cytoplasm and outside the cell. Therefore, release of this intracellular juice rich in sugars may cause the higher adhesion to the texture analyser probe.…”
Section: Impact Of Pef On Carrot Texturementioning
confidence: 99%
“…Additionally, changes in cell walls could also cause differences in the water absorbed into the polysaccharides network which affect other textural and sensory perception properties. [49] Electropermeabilisation and cytoplasmic content leakage could also increase adhesiveness of PEF-treated carrots since Aguiló-Aguayo et al [50] reported that cellular content moved from vacuoles to cytoplasm and outside the cell. Therefore, release of this intracellular juice rich in sugars may cause the higher adhesion to the texture analyser probe.…”
Section: Impact Of Pef On Carrot Texturementioning
confidence: 99%
“…Recently TD-NMR has been employed to investigate the cell walls and membrane disruption and water mobility in the plant tissue subjected to PEF treatment (Ersus, Oztop, McCarthy, & Barrett, 2010;Aguiló-Aguayo, Downey, Keenana, Lyng, Brunton, & Rai, 2014). Ersus et al (2010) were able to follow the changes of T 2 relaxation times from two different cell compartments namely cytoplasm and vacuoles.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, different transverse relaxation time T 2 components represented water in different mobile states in ginger samples rich in water (approximately 90%, Table 1), and longer T 2 relaxation times indicated more mobile water. In a low-field NMR study of carrot tissue, 37 three T 2 components, T 2a (10.3 ms), T 2b (54.2 ms), and T 2c (318 ms), were observed and assigned as water under three different combination states to distinguish the different degrees of tightness, i.e., water bound to rigid components of cell walls, water in extra-cellular compartments or cytosol and water in vacuoles, respectively. In our present study, the assignment of relaxation time T 2 components was more complicated for Henan gingers, which exhibited significantly different T 2 components than those of the other four ginger cultivars.…”
Section: ■ Results and Discussionmentioning
confidence: 99%